2020
DOI: 10.21037/gs-20-426
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management of thyroid aspirates diagnosed as atypia of undetermined significance in the Philippines

Abstract: Although the cytologic criteria of atypia of undetermined significance (AUS) are defined in The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC), there is heterogeneity in its prevalence, utilization, interpretation, and management. To determine the current practices of physicians of various specialties in the management of thyroid lesions reported as AUS in fine-needle aspirates in the Philippines, a survey consisting of eighteen questions was sent to physicians of varied specialties. Survey quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It is a well-known fact that there are racial/ethnic differences in the incidence and prognosis of thyroid cancer. Abelardo et al reported that the rates of AUSrelated thyroid malignancies in the Philippines and other Asian countries are much higher than in the general literature (11). This condition demonstrates that Bethesda Classification's category rates may vary in different countries.…”
Section: Süleyman Demirel üNiversitesi Tıp Fakültesi Dergisimentioning
confidence: 84%
“…It is a well-known fact that there are racial/ethnic differences in the incidence and prognosis of thyroid cancer. Abelardo et al reported that the rates of AUSrelated thyroid malignancies in the Philippines and other Asian countries are much higher than in the general literature (11). This condition demonstrates that Bethesda Classification's category rates may vary in different countries.…”
Section: Süleyman Demirel üNiversitesi Tıp Fakültesi Dergisimentioning
confidence: 84%
“…Ogmen et al [11] reported 5.4% AUS cases in their study and 29.3% of those cases were histopathologically malignant. Study by Yassa et al 14 showed that repeat FNA can lead to 80% definitive diagnosis, however risk of inconclusive readings, nondiagnostic and AUS can occur in 20% -49.1% of nodules with previous AUS FNA readings [6,12] Core needle biopsy (CNB) was recently introduced as a safe and effective procedure in diagnosing indeterminate thyroid nodules to prevent overtreatment. Some studies reported that CNB can classify as much as 98% of indeterminate thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al [14] reported that 50% of AUS cases become benign. Their center recommended a triage procedure of repeat FNA, US and BRAFV600E gene mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence and malignancy rates of AUS/FLUS vary widely in recent studies, ranging from 0.8% to 28% and from 6% to 48%, respectively ( 2 , 4 , 5 ). Currently, there is no consensus on a standardized clinical approach for the treatment of these nodules ( 6 ). The 2015 American Thyroid Association (ATA) guidelines recommend repeat FNA ( 7 ).…”
Section: Introductionmentioning
confidence: 99%